Rancang Bangun Oil System untuk Turbocharger Gas Turbine Engine Dengan Inducer Diameter 1,75 Inch - Noval Dwi Kurnianto; Wira Gauthama; Zulham Hidayat (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
Manufacturing of gas turbine engine was started by identification of some components and systems involve in building the gas turbine engine. A turbocharger which consist of turbine and compressor as the main part was taken to make a turbine and compressor in Gas turbine engine. Those component is also the essential part of the machine. To operate the gas turbine engine, it is important to design some system such as Oil system, fuel System, Ignition System, combustion chamber, and others. In this design project the writer obtains the task to design the oil system that fit and suitable for this type of gas turbine engine. Any issue related to this design such as how to decide the viscosity of the oil, calculate critical pressure of bearing, calculate mass of the oil fluid, head pressure of the pump and reservoir capacity. The final outcome of this design is correct supply of the oil flow which is used to lubricate shaft bearing in gas turbine engine. This system also prevent the machine from over heating that can degrade components of the engine due to metal to metal contact. From the final calculation found 37 psi oil pressure is needed to lubricate shaft bearing and can maintain the continuous operation of the engine.